2016
DOI: 10.1021/acs.analchem.5b04288
|View full text |Cite
|
Sign up to set email alerts
|

Insertable Fast-Response Amperometric NO/CO Dual Microsensor: Study of Neurovascular Coupling During Acutely Induced Seizures of Rat Brain Cortex

Abstract: This paper reports the fabrication of an insertable amperometric dual microsensor and its application for the simultaneous and fast sensing of NO and CO during acutely induced seizures of living rat brain cortex. NO and CO are important signaling mediators, controlling cerebrovascular tone. The dual NO/CO sensor is prepared based on a dual microelectrode having Au-deposited Pt microdisk (WE1, 76 μm diameter) and Pt black-deposited Pt disk (WE2, 50 μm diameter). The different deposited metals for WE1 and WE2 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 59 publications
(102 reference statements)
1
66
0
Order By: Relevance
“…Its capabilities to reach neurons that are 1.5 mm beneath the cerebral cortex and record or stimulate 100 different deep brain sites were ground breaking toward brain science. Other forms of large array probes consisted of microwires39 or metalized microdisks 130. However, long‐term implantation suffered from astroglial response and fibrous encapsulation of the probes, leading to limitations in chronic applications, such as the impedance rise of microelectrodes 113,114,131.…”
Section: Injectable Systems For the Brainmentioning
confidence: 99%
“…Its capabilities to reach neurons that are 1.5 mm beneath the cerebral cortex and record or stimulate 100 different deep brain sites were ground breaking toward brain science. Other forms of large array probes consisted of microwires39 or metalized microdisks 130. However, long‐term implantation suffered from astroglial response and fibrous encapsulation of the probes, leading to limitations in chronic applications, such as the impedance rise of microelectrodes 113,114,131.…”
Section: Injectable Systems For the Brainmentioning
confidence: 99%
“…Contrastively, only a few studies have been reported for electrochemical CO sensors aiming at biological applications due to selectivity problems [ 26 , 27 ]. Our group has developed NO/CO dual sensors for simultaneous NO and CO detections, and applied to in vivo and in vitro studies on rat kidneys and rat brains [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, high performance NO/CO dual [ 30 ] and new septuple microsensors were used for monitoring real-time NO and CO changes during glutamate-evoked neuronal activation in vitro. NO and CO were measured in a monolayer of a differentiated SH-SY5Y, which is a widely used dopaminergic neuronal cell type for in vitro model [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anumber of microelectrodes have been introduced for in vitro or in vivo applications [6][7][8][9][10][11][12][13] since electric signals from cultured cells were recorded by means of the microelectrode array 40 years ago. [14,15] Thes urface areas of microelectrodes are typically less than 0.01 mm 2 because as mall electrode area is advantageous for stimulatingt he specific tissue near which it is implanted, and also for recording neural signals with high spatialresolution.…”
Section: Introductionmentioning
confidence: 99%